2019
DOI: 10.1101/509521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glia-neuron interactions underlie state transitions to generalized seizures

Abstract: Brain activity and connectivity alter drastically during epileptic seizures. Throughout this transition, brain networks shift from a balanced resting state to a hyperactive and hypersynchronous state, spreading across the brain. It is, however, less clear which mechanisms underlie these state transitions. By studying neuronal and glial activity across the zebrafish brain, we observed striking differences between these networks. During the preictal period, neurons displayed a small increase in synchronous activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 104 publications
(137 reference statements)
6
41
0
Order By: Relevance
“…In the hippocampus, astrocytes can be intermediates between cholinergic input and interneurons (Pabst et al, 2016). Glial cells in zebrafish are activated before and during generalized seizures (Verdugo et al, 2019). These and other studies (Adamsky et al, Ding et al, 2013;Paukert et al, 2014; Poskanzer and Yuste, 2016; Srinivasan et al, 2015) point to an integrated role for astrocytes in information processing in brain circuits.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the hippocampus, astrocytes can be intermediates between cholinergic input and interneurons (Pabst et al, 2016). Glial cells in zebrafish are activated before and during generalized seizures (Verdugo et al, 2019). These and other studies (Adamsky et al, Ding et al, 2013;Paukert et al, 2014; Poskanzer and Yuste, 2016; Srinivasan et al, 2015) point to an integrated role for astrocytes in information processing in brain circuits.…”
Section: Discussionmentioning
confidence: 85%
“…They can, in turn, influence other neurons through multiple mechanisms (Bazargani and Attwell, 2016), such as transmitter release (Araque et al, 2014) or modulation of extracellular potassium concentration (Haydon and Nedergaard, 2014;Wang et al, 2015). They play a role in controlling the states of neural networks, perform spatial and temporal integration, and can underlie slow shifts in brain states (Araque et al, 2014) like sleep and seizures (Kjaerby et al, 2017;Verdugo et al, 2019). Calcium signals in astrocytes are triggered by sensory input and behavior (Bekar et al, 2008;Ma et al, 2016;Paukert et al, 2014;Schummers et al, 2008;Srinivasan et al, 2015;Verkhratsky et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, mice lacking the glutamate transporter EAAT2 exhibit epileptic seizures due to excessive glutamate (Tanaka et al, 1997). In line with this, breakdown of astroglia‐neuron interactions during epileptic seizures in zebrafish coincide with an excessive glutamate release (Diaz Verdugo et al, 2019).…”
Section: The Role Of Astroglia In Neural Circuit Function and Animal mentioning
confidence: 78%
“…One possibility is that early spontaneous activity might be driven by glia (Zhang et al, 2019) or other support cells (Babola et al, 2018), which usually generate slow bursts of activity. In fact, it was previously shown that astrocytes can modulate the bursting activity in the rodent habenula and astroglia activation in zebrafish can excite nearby neurons (Verdugo et al, 2019). Alternatively, it is possible that as the habenula develops, synaptic connections between habenular neurons become more mature.…”
Section: Discussionmentioning
confidence: 99%
“…Every recording was manually checked for motion and corresponding frames were discarded from further analysis. Individual neurons were semi-automatically detected using a pattern recognition as previously described (Jetti et al, 2014;Reiten et al, 2017;Verdugo et al, 2019). Once neurons were detected, their locations were individually tracked during the recording.…”
Section: Discussionmentioning
confidence: 99%